The Effects of the Melatonin Treatment on the Oxidative Stress and Apoptosis in Diabetic Eye and Brain - Tuğba Gürpınar; Nuran Ekerbiçer; Nazan Uysal; Turgay Barut; Figen Tarakçı; M. Ibrahim Tuglu (The Scientific World Journal)
Oxidative stress plays an important role in the development of complications in diabetes mellitus. Antioxidant therapy has been thought to decrease oxidative stress. The objective of the present study was to explore the effects of melatonin (MLT) on oxidative stress in diabetic rat eye and brain tissue by using immunohistochemical methods. Diabetes was induced by streptozotocin, (STZ, 55 mg/kg/i.p) in adult rats. MLT was given 10 mg/kg/i.p once a day for 2 weeks beginning from the sixth week. Six weeks later, rats were divided into three groups: control (CR), STZ-induced diabetic (STZ), and STZ-induced diabetic group received melatonin (STZ+MLT). Although no significant difference was observed with respect to antioxidant status, NOS activity tended to be higher in the untreated diabetic rats than in the treated rats. It was observed that MLT treatment improved the histopathological changes including apoptosis and oxidative stress in brain and eye in diabetic rat.